Concept of indicative strategic program management of the umbrella industrial EICSG-ecosystem of Industry 5.0 - Babkin Aleksandr; Batukova Louisa; Shkarupeta Elena (π-Economy)
The article is devoted to the development of fundamental and applied aspects of indicative strategic programming, providing the formation of the organizational foundations of the cyber-information development of industry. The focus of the research is on developing the concept of the organizational mechanism for software cyber-information management of the umbrella industrial EICSG-ecosystem. The relevance of the study is determined by the objectively necessary transition of modern industry to Industry 5.0, an organic and necessary component of which are umbrella industrial EICSG-ecosystems. The purpose of the research is to develop the organizational mechanism for indicative strategic software management of the umbrella industrial EICSG-ecosystem in a three-dimensional basis. The study is implemented in the paradigm of organizational systems engineering. But since the categorical apparatus of this modern scientific direction in the subject area of social and economic-administrative sciences is insufficiently developed, this paper proposes a new consideration of such concepts as the strategic perspective and the model of dynamics of the organizational and historical evolution of the economic and business mechanism. The work is fundamental and applied. This article: 1) develops the ideas of the classics, who formed the theory of universal organization and the theory of systems, including K.E. Tsiolkovsky, A.A. Bogdanov, L. von Bertalanffy; 2) develops the basis for the organizing a cybernetic approach to management at the level of mesosystems of the economic and business mechanism in the development of the conceptual foundations of the cybernetic approach, proposed in the works of N. Wiener, W. Ross Ashby, A.S. Beer; 3) substantiates the key parameters of strategic programming of the new umbrella industrial EICSG-ecosystem, which is necessary for the transition to the integral cyber-physical society. The novelty of the scientific research consists in the development of a mechanism for indicative strategic program management of the umbrella industrial EICSG-ecosystem in a three-dimensional basis. In particular, the characteristic of the umbrella industrial EICSG-ecosystem's own basis is given: in a real (institutional) modality; in a structural and architectural modality; in an information modality. The specified bases of the EICSG-ecosystem are projections of its integrity. Each basis is organizationally unique and must be formed as an independent component in organic connection with the other two components. This approach ensures the multidimensionality of the created mechanism of indicative strategic program management of the umbrella industrial EICSG-ecosystem of Industry 5.0.